Bioactive butenolides from Melodorum fruticosum - Patoomratana Tuchinda (2018)
From leaves and branches of Melodorum fruticosum, five butenolides have been isolated: (4Z)-6-acetoxy-7-benzoyloxy-2,4-heptadien-4-olide, (4E)-6-acetoxy-7-benzoyloxy-2,4-heptadien-4-olide, (4Z)-7-benzoyloxy-6-hydroxy-2,4-heptadien-4-olide, (4E)-7-benzoyloxy-6-hydroxy-2,4-heptadien-4-olide and (4Z)-6-benzoyloxy-7-hydroxy-2,4-heptadien-4-olide. In addition, two known flavonoids (chrysin, pinocembrin) and benzoic acid were isolated. All butenolides showed cytotoxic activities in several tumour cell lines. The structures of the isolated compounds were elucidated by spectroscopic methods. © 1991.